WAKTU, RUANG, DAN SEJARAH DALAM NOVEL BOERON DARI DIGOEL - Asep Rahmat Hidayat (SAWERIGADING, 2018)
Abstract Historical literature is a literary work that contains elements of history. Boeron dari Digoel  includes a historical novel written by historical figures as well. This study aims to reveal the way of time and space narrated by the author, so the historical aspect revealed from the novel. The method used is qualitative method with content analysis technique. The results show the time narrated in the colonial period between 1927-1929. Space is narrated in the region of Boven Digul in Papua. Both aspects reveal the history of discarding Indonesian historical figures to Boven Digul by the Dutch East Indies colonial government. The struggle was experienced by the novelist Boeron of Digoel..Keywords: historical novel, space, time, history